Polymeric and non‐crosslinked acid self‐thickening agent based on hydrophobically associating water‐soluble polymer during the acid rock reaction. Issue 36 (11th May 2019) - Tian, Haiyang; Quan, Hongping; Huang, Zhiyu; Duan, Wenmeng; Deng, Shunjie
ABSTRACT: Different from traditional crosslinked polymer diverting agents, a polymeric and non‐crosslinked acid self‐thickening agent (ZPAM) based on hydrophobically associating water‐soluble polymer of acrylamide (AM), [2‐(methacryloyloxy)ethyl]trimethylammonium chloride (DMC) and N, N ′‐dimethyl octadecyl allyl ammonium chloride (DOAC) was synthesized. The apparent viscosity variation of ZPAM acid solutions in acid rock reaction and rheological properties of ZPAM spent acid solutions were studied. Results showed that ZPAM acid solutions demonstrated good uninterruptedly thickening ability from low apparent viscosity to high apparent viscosity during the acid rock reaction. Meanwhile, ZPAM spent acid solutions showed good shear resistance, viscoelasticity and high temperature resistance. The thickening mechanism of ZPAM acid solutions during the acid rock reaction was explained by apparent viscosity change, rheological properties of simulative ZPAM acid solutions, and ZPAM aqueous solutions with different concentrations of CaCl2 . The results showed increasing calcium chloride concentration enhanced the hydrophobic association strength of the thickener solution, resulting in increasing solution viscosity, in other words, the self‐thickening agent showed excellent salt resistance and acid resistance. In addition, the change of association strength of ZPAM acid solutions during the acid rock reaction was further confirmed via environmental scanning electron micrographs and UV spectrum. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47907. Abstract : Thickening process of self‐thickening agent solution during the acid rock reaction.